Quality and Cost of Diabetes Mellitus Care in Community Health Centers in the United States. - Patrick Richard (PLoS ONE, 2015)
To examine variations in the quality and cost of care provided to patients with diabetes mellitus by Community Health Centers (CHCs) compared to other primary care settings.We used data from the 2005-2008 Medical Expenditure Panel Survey (N = 2,108). We used two dependent variables: quality of care and ambulatory care expenditures. Our primary independent variable was whether the respondent received care in a Community Health Centers (CHCs) or not. We estimated logistic regression models to determine the probability of quality of care, and used generalized linear models with log link and gamma distribution to predict expenditures for CHC users compared to non-users of CHCs, conditional on patients with positive expenditures.Results showed that variations of quality between CHC users and non-CHC users were not statistically significant. Patients with diabetes mellitus who used CHCs saved payers and individuals approximately $1,656 in ambulatory care costs compared to non-users of CHCs.These findings suggest an opportunity for policymakers to control costs for diabetes mellitus patients without having a negative impact on quality of care.